Self-healing ceramic-based composite material with continuous network structure and preparation method of self-healing ceramic-based composite material
By using a blended precursor formed by liquid polycarbosilane and polymethyl methacrylate and high-pressure curing/cracking integration technology, SiC ceramic matrix with continuous network structure and SiBCN ceramic matrix with self-healing function were prepared, which solved the problem of poor antioxidant performance of C/SiC ceramic matrix composites at high temperatures, and achieved efficient self-healing and antioxidant effect.
Patent Information
- Application Number
- CN202411717890.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
The existing C/SiC ceramic matrix composite materials have poor antioxidant performance in the range of 1000°C to 1400°C, resulting in serious oxidation and weight loss in high-temperature aerobic environment.
Liquid polycarbosilane and polymethyl methacrylate are used to form a blend precursor, and SiC ceramic matrix with a continuous network structure is prepared through the impregnation/curing/cracking PIP process, and SiBCN ceramic matrix with self-healing function is prepared through high-pressure curing/cracking integrated technology to form a SiC/SiBCN ceramic matrix composite material.
It significantly improves the antioxidant performance of ceramic matrix composite materials, realizes the self-healing and antioxidant function under high-temperature oxidation conditions, and effectively protects the carbon fiber from oxidation.
Smart Images

Figure CN119528597A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic-based composite material preparation, and in particular relates to a self-healing ceramic-based composite material with a continuous network structure and a preparation method thereof. Background Art
[0002] Carbon fiber toughened silicon carbide ceramic matrix composite material is a ceramic matrix composite material with continuous carbon fiber as toughening phase and silicon carbide ceramic as matrix. C / SiC composite material has high specific strength, good fracture toughness, fatigue performance and creep resistance at high temperature, and has attracted more and more attention from scientific and technological workers. In a high-temperature aerobic environment, C / SiC composite material mainly prevents oxygen from continuing to oxidize the composite material by oxidizing the matrix to generate a dense SiO2 film layer with low oxygen diffusion rate. At 1000℃~1400℃, because the oxidation product SiO2 has not yet melted, it is impossible to form a film to protect the carbon fiber and the matrix, causing the C / SiC composite material to fail due to severe oxidation weight loss.
[0003] Therefore, how to improve the long-term antioxidant properties of C / SiC ceramic-based composites at 1000℃~1400℃ is a key issue for silicon carbide ceramic-based composites to have reusable performance in high-temperature aerobic environments. Summary of the invention
[0004] In order to solve one or more technical problems existing in the prior art, the present invention provides a self-healing ceramic-based composite material with a continuous network structure and a preparation method thereof.
[0005] In a first aspect, the present invention provides a method for preparing a self-healing ceramic-based composite material having a continuous network structure, the method comprising the following steps:
[0006] (1) Preparing a pyrolytic carbon (PyC) layer on the surface of the carbon fiber of the carbon fiber preform, and then preparing (BN / SiC) on the basis of the pyrolytic carbon (PyC) layer n Alternating interface layers, resulting in PyC(BN / SiC) n Reinforcement of the interface layer;
[0007] (2) Liquid polycarbosilane and polymethyl methacrylate are prepared into a blended precursor, and the blended precursor is used as an impregnation liquid for the PyC (BN / SiC) n The reinforcement of the interface layer is impregnated to obtain a material including a SiC ceramic matrix having a continuous network structure through a PIP process of impregnation / solidification / cracking;
[0008] (3) subjecting the material including the SiC ceramic matrix having a continuous network structure to a first high temperature treatment;
[0009] (4) impregnating the material after the first high-temperature treatment with a polyborosilazane precursor as an impregnation liquid, and obtaining a material including a SiBCN ceramic matrix with a self-healing function through an impregnation / curing / cracking PIP process;
[0010] (5) The material including the SiBCN ceramic matrix having a self-healing function is subjected to a second high-temperature treatment to obtain a self-healing ceramic-based composite material having a continuous network structure.
[0011] Preferably, the carbon fiber preform is a needle-punched structure, a stitched structure, a 2.5D structure or a puncture structure; and / or the volume fraction of the carbon fiber in the carbon fiber preform is 25-50%.
[0012] Preferably, n represents the number of BN / SiC layers, n≥1 and is a natural number; the thickness of the pyrolytic carbon PyC layer is 30-80 nm; the thickness of the single BN layer is 50-250 nm; and / or the thickness of the single SiC layer is 50-200 nm.
[0013] Preferably, step (1) comprises the following sub-steps:
[0014] (a) placing a carbon fiber preform in a first atmosphere including propane and argon for deposition to obtain a first sample with a pyrolytic carbon (PyC) layer deposited on the surface;
[0015] (b) placing the first sample in a second atmosphere including boron trichloride, ammonia, hydrogen and nitrogen for deposition to obtain a second sample with a BN layer deposited on the surface;
[0016] (c) placing the second sample in a third atmosphere including trichloromethylsilane, argon and hydrogen for deposition to obtain a third sample with a SiC layer deposited on the surface;
[0017] (d) repeating step (b) and step (c) n-1 times, then heating to 1200-1400° C. and keeping the temperature for 1-4 hours to obtain the PyC (BN / SiC) n The reinforcement of the interface layer.
[0018] Preferably, in step (a), the molar ratio of the propane to the argon is 1:(1-2), the deposition temperature is 900-1100°C, and the deposition pressure is 5-10 kPa; in step (b), the molar ratio of the boron trichloride to the ammonia is 1:(2-3), the deposition temperature is 750-900°C, and the deposition pressure is 5-10 kPa; and / or in step (c), the molar ratio of the trichloromethylsilane to the hydrogen is 1:(2-3); the deposition temperature is 1000-1200°C, and the deposition pressure is 5-10 kPa.
[0019] Preferably, the blended precursor is prepared as follows: first, polymethyl methacrylate is dissolved in a mixed solvent consisting of acetone and xylene to obtain a polymethyl methacrylate solution, and then the polymethyl methacrylate solution is added to liquid polycarbosilane and stirred for 10 to 20 hours, and then allowed to stand for 12 to 24 hours to obtain a blended precursor; and / or the mass ratio of the liquid polycarbosilane to polymethyl methacrylate is 10:(3 to 15).
[0020] Preferably, in step (2): the impregnation is first vacuum impregnation and then high-pressure impregnation, the pressure of the vacuum impregnation is 10-200 Pa, the time is 2-4 h, the pressure of the high-pressure impregnation is 2-5 MPa, and the time is 2-4 h; the curing is first curing at 100-120°C for 1-4 h, and then curing at 150-180°C for 1-4 h, and the curing pressure is 2-5 MPa; the pyrolysis is pyrolysis at 300-320°C for 1-3 h, 340-360°C for 1-3 h, 380-400°C for 1-3 h and 1000-1500°C for 2-6 h, and the heating rate within the pyrolysis temperature range of 300-400°C is 0.2-0.4°C / min; and / or the PIP process is repeated 2 to 4 times.
[0021] Preferably, in step (4): the impregnation is first vacuum impregnation and then high-pressure impregnation, the pressure of the vacuum impregnation is 10-200 Pa, the time is 2-4 h, the pressure of the high-pressure impregnation is 2-5 MPa, and the time is 2-4 h; the temperature of the curing is 180-220° C., the time of the curing is 1-4 h, and the pressure of the curing is 3-6 MPa; the temperature of the pyrolysis is 1000-1300° C., the time of the pyrolysis is 2-6 h, and the pressure of the pyrolysis is 3-6 MPa; and / or the PIP process is repeated 3 to 5 times.
[0022] Preferably, the temperature of the first high temperature treatment and / or the second high temperature treatment is 1400-1500° C., and the time is 2-4 hours.
[0023] In a second aspect, the present invention provides a self-healing ceramic-based composite material having a continuous network structure obtained by the preparation method described in the first aspect of the present invention; preferably, the linear ablation rate of the self-healing ceramic-based composite material having a continuous network structure in an oxyacetylene ablation test is less than 1×10 -4 mm / s.
[0024] Compared with the prior art, the present invention has at least the following beneficial effects:
[0025] (1) The present invention uses liquid polycarbosilane and polymethyl methacrylate (PMMA) to form a blended precursor. By adjusting the amount of PMMA added, a SiC ceramic matrix with a continuous network structure and different porosities can be obtained.
[0026] (2) The present invention adopts high-pressure curing / cracking integrated preparation technology to obtain a high-density SiBCN ceramic matrix with self-healing function, effectively fill the continuous network structure of the SiC ceramic matrix in the composite material, and realize the organic combination of the continuous network structure SiC ceramic matrix and the high-density SiBCN ceramic matrix, so that the prepared self-healing ceramic-based composite material can give full play to the low melting point characteristics of B2O3 generated after oxidation of the B element in the SiBCN ceramic matrix at high temperature. The oxidation product B2O3 and SiO2 can form a low-viscosity solid solution to achieve self-healing of matrix cracks and holes, thereby effectively protecting the carbon fiber from oxidation, significantly improving the antioxidant properties of the ceramic-based composite material and realizing the self-healing antioxidant function under high-temperature oxidation conditions, thereby effectively solving the problem of poor long-term antioxidant performance of the ceramic-based composite material at a temperature of 1000°C to 1400°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a SEM image of a material including a SiC ceramic matrix having a continuous network structure obtained in Example 1 of the present invention;
[0028] Figure 2 is a SEM image of a material including a SiC ceramic matrix prepared in Example 4 of the present invention;
[0029] Figure 3 is a SEM image of the ceramic-based composite material finally obtained in Comparative Example 6 of the present invention;
[0030] Figure 4 This is a SEM image of the ceramic-based composite material finally obtained in Comparative Example 7 of the present invention. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] In a first aspect, the present invention provides a method for preparing a self-healing ceramic-based composite material having a continuous network structure, the method comprising the following steps:
[0033] (1) Preparing a pyrolytic carbon (PyC) layer on the surface of the carbon fiber of the carbon fiber preform, and then preparing (BN / SiC) on the basis of the pyrolytic carbon (PyC) layer n Alternating interface layers, resulting in PyC(BN / SiC) n A reinforcement of the interface layer; in the present invention, n represents the number of BN / SiC layers, n≥1 and is a natural number;
[0034] (2) Liquid polycarbosilane and polymethyl methacrylate (PMMA) are prepared into a blended precursor, and the blended precursor is used as an impregnation liquid for the PyC (BN / SiC) n The reinforcement of the interface layer is impregnated, and a material containing a SiC ceramic matrix with a continuous network structure is obtained by an impregnation / curing / cracking PIP process (i.e., impregnation curing cracking technology); in the present invention, the blended precursor is prepared by liquid polycarbosilane and PMMA in a certain proportion; when the impregnation is performed in step (2), the PyC (BN / SiC) n The reinforcement of the interface layer is completely immersed in the blended precursor; the present invention does not specifically limit the polymethyl methacrylate used, and a product that can be directly purchased or a product synthesized by an existing method can be used;
[0035] (3) subjecting the material including the SiC ceramic matrix having a continuous network structure to a first high temperature treatment; in the present invention, the first high temperature treatment is performed under an inert atmosphere, such as an inert atmosphere such as nitrogen and / or argon;
[0036] (4) using a polyborosilazane precursor (also referred to as a SiBCN precursor) as an impregnation liquid to impregnate the material after the first high-temperature treatment in step (3), and obtaining a material comprising a SiBCN ceramic matrix with a self-healing function (also referred to as a dense SiBCN ceramic matrix with a self-healing function or a high-density SiBCN ceramic matrix with a self-healing function) through an impregnation / curing / cracking PIP process; in step (4) of the present invention, the PIP process used is a vacuum / high-pressure impregnation and high-pressure curing / cracking integrated technology; when impregnating in step (4), the material after the first high-temperature treatment is completely immersed in the polyborosilazane precursor; the present invention does not specifically limit the polyborosilazane precursor (i.e., liquid polyborosilazane), and liquid polyborosilazane that can be directly purchased or liquid polyborosilazane prepared by an existing method can be used;
[0037] (5) subjecting the material including the SiBCN ceramic matrix with self-healing function to a second high-temperature treatment to obtain a self-healing ceramic matrix composite material with a continuous network structure; in the present invention, the second high-temperature treatment is carried out under an inert atmosphere, and the inert atmosphere is, for example, an inert atmosphere such as nitrogen and / or argon; the self-healing ceramic matrix composite material with a continuous network structure prepared by the present invention comprises a SiC ceramic matrix with a continuous network structure and a SiBCN ceramic matrix with self-healing function filled in the continuous network structure (a dense self-healing ceramic matrix), forming a dense SiC / SiBCN ceramic matrix in which the SiC ceramic matrix and the SiBCN ceramic matrix are uniformly distributed, so that the two ceramic matrices can synergistically exert the effects of high temperature resistance and antioxidant properties, and the uniformly distributed boron (B)-containing component (SiBCN ceramic matrix) fills the matrix microcracks to play a self-healing role, thereby improving the comprehensive antioxidant capacity of the matrix. The present invention selects liquid polycarbosilane and polymethyl methacrylate (PMMA) to form a blended precursor, and can obtain a SiC ceramic matrix with a continuous network structure. The high-pressure curing / cracking integrated preparation technology can be used to obtain a high-density SiBCN ceramic matrix with a self-healing function, and the continuous network structure of the SiC ceramic matrix in the composite material is effectively filled, thereby realizing the organic combination of the continuous network structure SiC ceramic matrix and the high-density SiBCN ceramic matrix, so that the prepared self-healing ceramic-based composite material can give full play to the low melting point characteristics of B2O3 generated after oxidation of the B element in the SiBCN ceramic matrix at high temperature, and the oxidation product B2O3 and SiO2 can form a low-viscosity solid solution to realize self-healing of matrix cracks and holes, thereby effectively protecting the carbon fiber from oxidation, significantly improving the antioxidant performance of the ceramic-based composite material and realizing the self-healing antioxidant function under high-temperature oxidation conditions, thereby effectively solving the problem of poor long-term antioxidant performance of the ceramic-based composite material at a temperature of 1000°C to 1400°C.
[0038] According to some preferred embodiments, the carbon fiber preform is a needle-punched structure, a stitched structure, a 2.5D structure or a puncture structure; and / or the volume fraction of the carbon fiber in the carbon fiber preform is 25-50%.
[0039] According to some preferred embodiments, n represents the number of BN / SiC layers, n≥1 and is a natural number; the thickness of the pyrolytic carbon PyC layer is 30-80 nm (for example, 30, 40, 50, 60, 70 or 80 nm); the thickness of the single-layer BN layer is 50-250 nm (for example, 50, 80, 100, 120, 150, 180, 200, 220 or 250 nm), preferably 50-150 nm; and / or the thickness of the single-layer SiC layer is 50-200 nm (for example, 50, 80, 100, 120, 150, 180 or 200 nm), preferably 50-150 nm.
[0040] According to some preferred embodiments, step (1) comprises the following sub-steps:
[0041] (a) placing a carbon fiber preform in a first atmosphere including propane and argon for deposition to obtain a first sample with a pyrolytic carbon (PyC) layer deposited on the surface;
[0042] (b) placing the first sample in a second atmosphere including boron trichloride, ammonia, hydrogen and nitrogen for deposition to obtain a second sample with a BN layer deposited on the surface;
[0043] (c) placing the second sample in a third atmosphere including trichloromethylsilane, argon and hydrogen for deposition to obtain a third sample with a SiC layer deposited on the surface;
[0044] (d) repeating step (b) and step (c) n-1 times, that is, in the present invention, step (b) and step (c) are performed n times in total, and then heating to 1200-1400° C. and keeping the temperature (high temperature treatment) for 1-4 hours to obtain the PyC (BN / SiC) n Reinforcement of the interface layer; in the present invention, the heat preservation in step (d) is carried out under an inert atmosphere, such as an argon and / or nitrogen atmosphere.
[0045] In the present invention, the PyC (BN / SiC) n The interface layer is a composite interface layer. In order to match the thermal properties of carbon fiber, a pyrolytic carbon PyC layer is first prepared; the PyC, BN, and SiC interface layers can obtain coatings of different thicknesses by adjusting the deposition time.
[0046] According to some preferred embodiments, in step (a), the molar ratio of the propane to the argon is 1: (1-2), the deposition temperature is 900-1100°C, the deposition pressure is 5-10 kPa, and the deposition time is, for example, 5-15 h; in step (b), the molar ratio of the boron trichloride to the ammonia is 1: (2-3), the deposition temperature is 750-900°C, the deposition pressure is 5-10 kPa, and the deposition time is, for example, 5-15 h. Preferably, the boron trichloride, ammonia, hydrogen and nitrogen The molar ratio of the trichloromethylsilane, argon and hydrogen is 1: (2-3): (1.2-1.8): (2-3), preferably 1: 2.5: 1.5: 2.5; and / or in step (c), the molar ratio of the trichloromethylsilane and the hydrogen is 1: (2-3), the deposition temperature is 1000-1200° C., the deposition pressure is 5-10 kPa, and the deposition time is, for example, 10-25 h. Preferably, the molar ratio of the trichloromethylsilane, argon and hydrogen is 1: (2-3): (2-3), preferably 1: 2.5: 2.5.
[0047] In the present invention, the PyC, BN and SiC interface layers are all prepared by chemical vapor deposition process. In the same furnace, the PyC, BN and SiC interface layers can be obtained respectively by adjusting the temperature of the equipment and the type of gas introduced. Among them, the pyrolytic carbon PyC layer is the first layer, which solves the thermal adaptation problem between the coating and the carbon fiber. At the same time, the thickness of the pyrolytic carbon PyC layer is controlled to be 30-80nm, which can better play the role of the transition layer. BN is the second layer. Since the BN interface layer has a layered structure similar to pyrolytic carbon, it has good adaptability and bonding strength with the first pyrolytic carbon PyC layer. Preferably, the thickness of the single-layer BN layer is controlled to be 50-150nm, and the SiC interface layer is an anti-oxidation coating commonly used in ceramic-based composite materials. Preferably, the thickness of the single-layer SiC layer is controlled to be 50-150nm; in the present invention, SiC and BN interface layers are used alternately, and B2O3 and SiO2 can be generated under 1000-1400°C oxidation conditions, and a borosilicate glass phase can be generated in situ, which effectively protects the carbon fiber from oxidation, gives full play to the anti-oxidation effect of the multi-layer interface layer, and is beneficial to improving the long-term anti-oxidation performance of the ceramic-based composite material in the temperature range of 1000-1400°C.
[0048] According to some preferred embodiments, the blended precursor is prepared as follows: first, polymethyl methacrylate is dissolved in a mixed solvent consisting of acetone and xylene to obtain a polymethyl methacrylate solution (PMMA solution), and then the polymethyl methacrylate solution is added to liquid polycarbosilane and stirred for 10 to 20 hours (for example, 10, 12, 15, 18 or 20 hours), and then allowed to stand for 12 to 24 hours (for example, 12, 15, 18, 20 or 24 hours) to obtain a blended precursor; in the present invention, preferably, in the mixed solvent, the volume ratio of acetone to xylene is 10: (1 to 2); preferably, the mass fraction of polymethyl methacrylate contained in the obtained polymethyl methacrylate solution is 50 to 70%.
[0049] According to some preferred embodiments, the mass ratio of the liquid polycarbosilane to the polymethyl methacrylate contained in the polymethyl methacrylate solution is 10:(3-15), that is, the mass ratio of the liquid polycarbosilane to polymethyl methacrylate is 10:(3-15) (for example, 10:3, 10:4, 10:5, 10:6, 10:7, 10:8, 10:9, 10:10, 10:11, 10:12, 10:13, 10:14 or 10:15).
[0050] According to some specific embodiments, the PMMA is a solid powder, which is first dissolved in a mixed solvent consisting of acetone and xylene, and the PMMA solution obtained after the dissolution is continuously added to the liquid polycarbosilane, and mechanically stirred and mixed evenly at room temperature (i.e., room temperature), and the stirring time is 10 to 20 hours. The evenly stirred solution is poured into a watch glass, placed in a fume hood, and left at room temperature for 12 to 24 hours to mainly remove the acetone solvent (acetone evaporates quickly, xylene evaporates slowly, and the amount of volatilization is small), so as to obtain a blended precursor; in the present invention, the room temperature is, for example, room temperature of 15 to 35°C; the present invention does not specifically limit the speed of mechanical stirring, and those skilled in the art can make a conventional selection.
[0051] A key point of the present invention is to limit the mass ratio of liquid polycarbosilane to polymethyl methacrylate (PMMA) to 10:3-15, and obtain a blended precursor with different pore-forming agent addition amounts; the present invention finds that different addition amounts of the pore-forming agent (polymethyl methacrylate) can obtain pyrolysis products with different pore structures, thereby affecting the amount of the self-healing matrix in the final composite material and the continuity of the structure, and ultimately affecting the antioxidant properties of the composite material; when the addition amount of the pore-forming agent is small, the porosity and pore size of the obtained pyrolysis product are small, and as the addition amount of the pore-forming agent increases, the porosity and pore size gradually increase. When the mass ratio of liquid polycarbosilane to PMMA is 10:10, the pore size reaches a maximum value, and as the addition amount of the pore-forming agent further increases, the pore size remains substantially unchanged, and the porosity further increases; the blended precursor The controllable adjustment of the amount of pore-forming agent added in the body lays a good foundation for the subsequent preparation of a SiC ceramic matrix with a continuous network structure. The present invention finds that if the mass ratio of polymethyl methacrylate (PMMA) to liquid polycarbosilane is less than 3:10, the SiC ceramic matrix obtained after cracking does not have a continuous network structure; and if the mass ratio of polymethyl methacrylate (PMMA) to liquid polycarbosilane is greater than 15:10, the SiC ceramic matrix after cracking is a dispersed structure, and a continuous network structure cannot be formed. After multiple impregnation, curing and cracking, a ceramic matrix structure with a continuous network structure cannot be formed, which leads to a decrease in the antioxidant performance of the ceramic-based composite material. In addition, due to the excessively high PMMA content, the yield during the impregnation and cracking process is too low, the weight gain is slow, and the preparation cycle of the composite material is increased.
[0052] According to some preferred embodiments, in step (2), the impregnation is first vacuum impregnation and then high-pressure impregnation, the pressure of the vacuum impregnation is 10-200 Pa, the time is 2-4 hours, the pressure of the high-pressure impregnation is 2-5 MPa, and the time is 2-4 hours; the curing is first at 100-120° C. for 1-4 hours, and then at 150-180° C. for 1-4 hours, and the curing pressure is 2-5 MPa; the pyrolysis is sequentially pyrolyzed at 300-320° C. for 1-3 hours, 340-360° C. for 1-3 hours, and 380-400° C. for 1-4 hours. 3h and 1000-1500°C for 2-6h, and the heating rate during the cracking process at a cracking temperature of 300-400°C is 0.2-0.4°C / min; in the present invention, the cracking is carried out under an inert atmosphere such as nitrogen and / or argon, and the cracking is carried out under normal pressure; in the cracking process of the present invention, the heating rate for heating to other cracking temperatures can be, for example, 1-10°C / min, for example, the heating rate for heating to 1000-1500°C is 1-10°C / min; and / or the PIP process is repeated 2-4 times.
[0053] According to some specific embodiments, in step (2), the PIP process of impregnation / curing / cracking is:
[0054] (a) Using the blended precursor as the impregnation liquid for the PyC (BN / SiC) n The reinforcement of the interface layer is impregnated, wherein the impregnation is first vacuum impregnation and then high pressure impregnation, the pressure of the vacuum impregnation is 10-200 Pa, the time is 2-4 hours, and the pressure of the high pressure impregnation is 2-5 MPa, the time is 2-4 hours;
[0055] (b) curing after impregnation, wherein the curing is firstly curing at 100-120° C. for 1-4 hours, and then curing at 150-180° C. for 1-4 hours, and the curing pressure is 2-5 MPa;
[0056] (c) After curing, the pyrolysis is carried out in a high temperature treatment furnace under an inert atmosphere such as nitrogen and / or argon. During the pyrolysis process, the heating rate in the range of 300-400° C. is 0.2-0.4° C. / min, and the pyrolysis is carried out at 300-320° C. for 1-3 h, 340-360° C. for 1-3 h, 380-400° C. for 1-3 h, and finally at 1000-1500° C. for 2-6 h.
[0057] (d) Repeating steps (a) to (c) in sequence for a total of 2-4 impregnation / curing / cracking cycles to complete the preparation of a material comprising a SiC ceramic matrix having a continuous network structure.
[0058] Another key point of the present invention is to control the cracking process of the blended precursor; it is found that during the cracking process, the heating rate within the range of 300-400°C is very important for obtaining a SiC ceramic matrix with a continuous network structure; the present invention finds that 99% of PMMA decomposes into small molecular gas products within the temperature range of 300-400°C. If PMMA decomposes too quickly within this temperature range, it will cause severe shrinkage of the precursor and it is impossible to obtain a SiC network structure with a better structure; the present invention controls the heating and insulation parameters of 300-400°C, specifically, the heating rate within the range of 300-400°C is controlled to 0.2-0.4°C / min, and at the same time, 3 insulation points are set within the range of 300-400°C, and finally cracked at a high temperature of 1000-1500°C. The present invention finds that such a cracking process is conducive to obtaining a SiC ceramic matrix with a continuous network structure.
[0059] According to some preferred embodiments, the temperature of the first high temperature treatment is 1400-1500°C, and the time is 2-4 hours; another key point of the present invention is to carry out the first high temperature treatment. The present invention finds that after the first high temperature treatment, the SiC matrix can be cracked more fully, and at the same time, the SiC continuous network structure can be better maintained, which can provide a more effective impregnation channel for the subsequent polyborosilazane precursor.
[0060] According to some preferred embodiments, in step (4): the impregnation is first vacuum impregnation and then high-pressure impregnation, the pressure of the vacuum impregnation is 10-200 Pa, the time is 2-4 h, the pressure of the high-pressure impregnation is 2-5 MPa, and the time is 2-4 h; the temperature of the curing is 180-220°C, the time of the curing is 1-4 h, and the pressure of the curing is 3-6 MPa; the temperature of the cracking is 1000-1300°C, the time of the cracking is 2-6 h, and the pressure of the cracking is 3-6 MPa; the cracking is carried out under an inert atmosphere of nitrogen and / or argon; and / or the PIP process is repeated 3 to 5 times.
[0061] According to some specific embodiments, in step (4), the PIP process of impregnation / curing / cracking is:
[0062] (a) impregnating the material after the first high temperature treatment with a polyborosilazane precursor as an impregnation liquid, wherein the impregnation is first vacuum impregnation and then high pressure impregnation, the pressure of the vacuum impregnation is 10-200 Pa, the time is 2-4 hours, and the pressure of the high pressure impregnation is 2-5 MPa, and the time is 2-4 hours;
[0063] (b) curing after impregnation, wherein the curing temperature is 180 to 220° C., the curing time is 1 to 4 hours, and the curing pressure is 3 to 6 MPa;
[0064] (c) After solidification, the solidified solid is cracked in an inert atmosphere such as nitrogen and / or argon using a high pressure cracking furnace, wherein the cracking temperature is 1000-1300° C., the cracking time is 2-6 hours, and the cracking pressure is 3-6 MPa. In the present invention, unless otherwise specified, the heating rate to the cracking temperature and / or high temperature treatment temperature is 1-10° C. / min;
[0065] (d) Repeating steps (a) to (c) in sequence for a total of 3-5 impregnation / curing / cracking cycles to complete the preparation of the material containing the SiBCN ceramic matrix with self-healing function.
[0066] In the present invention, step (4) is carried out by vacuum / high-pressure impregnation / high-pressure curing / high-pressure cracking integrated molding technology, which uses a high-pressure cracking furnace. The process can only be loaded and unloaded from the furnace once. Compared with traditional high-pressure curing and cracking, one process cycle can save 2 to 3 days of time, for example; the cracking process uses high-pressure cracking technology, which can improve the density of the SiBCN matrix, thereby facilitating the acquisition of a highly dense ceramic-based composite material; in this step, after the polyborosilazane precursor is high-pressure cured, it is directly heated and cracked in situ, which can not only shorten the cycle but also obtain a highly dense SiBCN ceramic matrix.
[0067] According to some preferred embodiments, in step (5): the temperature of the second high temperature treatment is 1400-1500°C, and the time is 2-4h; another key point of the present invention is to carry out a second high temperature treatment. After the second high temperature treatment, the SiBCN ceramic matrix can be more fully cracked, and at the same time, the SiBCN matrix structure is more stable, which is beneficial to improving the high temperature oxidation resistance of the ceramic-based composite material.
[0068] In the second aspect, the present invention provides a self-healing ceramic-based composite material with a continuous network structure prepared by the preparation method described in the first aspect of the present invention; the self-healing ceramic-based composite material with a continuous network structure prepared by the present invention comprises a SiC ceramic matrix with a continuous network structure and a SiBCN ceramic matrix (a dense self-healing ceramic matrix) with a self-healing function filled in the continuous network structure, forming a dense SiC / SiBCN ceramic matrix in which the SiC ceramic matrix and the SiBCN ceramic matrix are uniformly distributed, so that the two ceramic matrices can synergistically play the role of high temperature resistance and oxidation resistance, and the uniformly distributed boron (B)-containing components fill the microcracks of the matrix to play a self-healing role, thereby improving the comprehensive antioxidant capacity of the matrix, which is manifested as a significant improvement in the long-term antioxidant performance of the ceramic-based composite material.
[0069] According to some preferred embodiments, the linear ablation rate of the self-healing ceramic-based composite material having a continuous network structure in an oxyacetylene ablation test is less than 1×10-4 mm / s.
[0070] The present invention will be further described below in conjunction with specific examples. However, it should be understood that these examples are only used to illustrate the present invention and do not constitute a limitation of the scope of the present invention. The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.
[0071] Example 1
[0072] ① Using a needle-punched structural carbon fiber preform, the fiber volume fraction of the needle-punched structural carbon fiber preform is 30%, preparing a pyrolytic carbon PyC layer on the surface of the carbon fiber of the needle-punched structural carbon fiber preform, and then preparing (BN / SiC) on the basis of the pyrolytic carbon PyC layer n Alternating interface layers, resulting in PyC(BN / SiC) n The reinforcement of the interface layer, wherein n=3; specifically: (a) placing the needle-punched structural carbon fiber preform in a first atmosphere including propane and argon (the molar ratio of propane to argon is 1:1.5) for deposition, the deposition temperature is 1000°C, the deposition pressure is 8kPa, and a first sample having a pyrolytic carbon PyC layer with a thickness of 60nm deposited on the surface is obtained; (b) placing the first sample in a second atmosphere including boron trichloride, ammonia, hydrogen and nitrogen (the molar ratio of boron trichloride, ammonia, hydrogen and nitrogen is 1:2.5:1.5:2.5) for deposition, the deposition temperature is 800°C, the deposition pressure is The pressure is 8 kPa, and a second sample with a BN layer of 120 nm thickness deposited on the surface is obtained; (c) the second sample is placed in a third atmosphere including trichloromethylsilane, argon and hydrogen (the molar ratio of trichloromethylsilane, argon and hydrogen is 1:2.5:2.5) for deposition, the deposition temperature is 1100°C, the deposition pressure is 8 kPa, and a third sample with a SiC layer of 120 nm thickness deposited on the surface is obtained; (d) steps (b) to (c) are repeated twice in sequence, and then the temperature is raised to 1300°C in an argon atmosphere and kept for 2 hours to obtain the PyC (BN / SiC) n Reinforcement of the interface layer.
[0073] ② A blended precursor is prepared by combining liquid polycarbosilane and polymethyl methacrylate (PMMA) in a mass ratio of 10:10; specifically, the polymethyl methacrylate (PMMA) solid powder is first dissolved in a mixed solvent consisting of acetone and xylene (the volume ratio of acetone to xylene is 10:1.5), and the polymethyl methacrylate solution obtained after the dissolution (the mass fraction of polymethyl methacrylate in the polymethyl methacrylate solution is 60%) is continuously added to the liquid polycarbosilane, and the mixture is stirred evenly at room temperature for 18 hours. The evenly stirred solution is poured into a watch glass, placed in a fume hood, and left at room temperature for 24 hours to obtain a blended precursor, wherein the mass ratio of the liquid polycarbosilane to the polymethyl methacrylate contained in the polymethyl methacrylate solution is 10:10.
[0074] ③ Using the blended precursor obtained in step ② as the impregnation liquid, the PyC (BN / SiC) obtained in step ① n The reinforcement of the interface layer is impregnated, and a material containing a SiC ceramic matrix with a continuous network structure is obtained by an impregnation / curing / cracking PIP process; specifically: (a) using the blended precursor as an impregnation liquid to impregnate the PyC (BN / SiC) n (a) impregnating the reinforcement of the interface layer, wherein the impregnation is first vacuum impregnation and then high-pressure impregnation, wherein the pressure of the vacuum impregnation is 100 Pa and the time is 3 h, and the pressure of the high-pressure impregnation is 3 MPa and the time is 3 h; (b) curing is performed after impregnation, wherein the curing is first cured at 110°C for 2 h and then cured at 160°C for 3 h, and the curing pressure is 3 MPa; (c) after curing, a high-temperature treatment furnace is used to perform normal pressure cracking in an argon inert atmosphere. During the normal pressure cracking process, the temperature is first increased to 300°C at a heating rate of 5°C / min and cracked at 300°C for 2 h, then increased to 350°C at a heating rate of 0.3°C / min and cracked at 350°C for 2 h, and then increased to 0.3°C / min at a heating rate of 0.3°C / min. (d) repeating steps (a) to (c) twice, performing a total of three impregnation / curing / cracking cycles to complete the preparation of a material comprising a SiC ceramic matrix having a continuous network structure; in this embodiment, liquid polycarbosilane and polymethyl methacrylate (PMMA) are used to form a blended precursor, and the blended precursor is cracked by a PIP process to form a porous network structure, that is, a material comprising a SiC ceramic matrix having a continuous network structure is obtained. The SEM image of the material comprising a SiC ceramic matrix having a continuous network structure prepared in this embodiment is as follows: Figure 1 shown.
[0075] ④ Subject the material obtained in step ③ comprising a SiC ceramic matrix having a continuous network structure to a first high-temperature treatment, wherein the first high-temperature treatment is carried out under an argon inert atmosphere at a temperature of 1450° C. and a time of 3 hours.
[0076] ⑤ Using a polyborosilazane precursor (liquid polyborosilazane) as an impregnation liquid to impregnate the material after the first high temperature treatment in step ④, and obtain a material containing a SiBCN ceramic matrix with a self-healing function through an impregnation / curing / cracking PIP process; specifically: (a) using a polyborosilazane precursor as an impregnation liquid to impregnate the material after the first high temperature treatment in step ④, the impregnation is first vacuum impregnation and then high pressure impregnation, the vacuum impregnation pressure is 100Pa, the time is 3h, the high pressure impregnation pressure is 3MPa, the time is 3h; (b) curing after impregnation, the curing temperature is 200℃, the curing time is 3h, and the curing pressure is 4MPa; (c) after curing, high-pressure cracking furnace is used for cracking under argon inert atmosphere, the cracking temperature is 1200℃, the cracking time is 3h, and the cracking pressure is 5MPa; (d) repeating steps (a) to (c) 3 times in sequence, for a total of 4 impregnation / curing / cracking cycles, to complete the preparation of the material containing the SiBCN ceramic matrix with self-healing function.
[0077] ⑥ Subject the material obtained in step ⑤ containing the SiBCN ceramic matrix with self-healing function to a second high-temperature treatment to obtain a self-healing ceramic-based composite material with a continuous network structure; the second high-temperature treatment is carried out under an argon inert atmosphere, the temperature of the second high-temperature treatment is 1450°C, and the time is 3 hours.
[0078] The self-healing ceramic-based composite material with a continuous network structure prepared in this embodiment was subjected to an oxyacetylene ablation test (the temperature of the material surface was 1400°C and the test time was 1000s). The linear ablation rate in the oxyacetylene ablation test was measured to be 0.6×10 -4 mm / s; the present invention also oxidizes the self-healing ceramic-based composite material with a continuous network structure prepared in this embodiment at 1400°C in an air atmosphere for 12 hours, and the weight loss rate results are shown in Table 1.
[0079] Example 2
[0080] Embodiment 2 is substantially the same as Embodiment 1, except that:
[0081] ② A blended precursor is prepared by combining liquid polycarbosilane and polymethyl methacrylate (PMMA) in a mass ratio of 10:3; specifically, the polymethyl methacrylate (PMMA) solid powder is first dissolved in a mixed solvent consisting of acetone and xylene (the volume ratio of acetone to xylene is 10:1.5), and the polymethyl methacrylate solution obtained after the dissolution (the mass fraction of polymethyl methacrylate in the polymethyl methacrylate solution is 60%) is continuously added to the liquid polycarbosilane, and the mixture is stirred and mixed evenly at room temperature for 18 hours. The evenly stirred solution is poured into a watch glass, placed in a fume hood, and left at room temperature for 24 hours to obtain a blended precursor, wherein the mass ratio of the liquid polycarbosilane to the polymethyl methacrylate contained in the polymethyl methacrylate solution is 10:3.
[0082] Example 3
[0083] Embodiment 3 is substantially the same as Embodiment 1, except that:
[0084] ② A blended precursor is prepared by combining liquid polycarbosilane and polymethyl methacrylate (PMMA) in a mass ratio of 10:15; specifically, the polymethyl methacrylate (PMMA) solid powder is first dissolved in a mixed solvent consisting of acetone and xylene (the volume ratio of acetone to xylene is 10:1.5), and the polymethyl methacrylate solution obtained after the dissolution (the mass fraction of polymethyl methacrylate in the polymethyl methacrylate solution is 60%) is continuously added to the liquid polycarbosilane, and the mixture is stirred and mixed evenly at room temperature for 18 hours. The evenly stirred solution is poured into a watch glass, placed in a fume hood, and left at room temperature for 24 hours to obtain a blended precursor, wherein the mass ratio of the liquid polycarbosilane to the polymethyl methacrylate contained in the polymethyl methacrylate solution is 10:15.
[0085] Example 4
[0086] Embodiment 4 is substantially the same as Embodiment 1, except that:
[0087] ② A blended precursor is prepared by combining liquid polycarbosilane and polymethyl methacrylate (PMMA) in a mass ratio of 10:1.5; specifically, the polymethyl methacrylate (PMMA) solid powder is first dissolved in a mixed solvent consisting of acetone and xylene (the volume ratio of acetone to xylene is 10:1.5), and the polymethyl methacrylate solution obtained after the dissolution (the mass fraction of polymethyl methacrylate in the polymethyl methacrylate solution is 60%) is continuously added to the liquid polycarbosilane, and the mixture is stirred evenly at room temperature for 18 hours. The evenly stirred solution is poured into a watch glass, placed in a fume hood, and left at room temperature for 24 hours to obtain a blended precursor, wherein the mass ratio of the liquid polycarbosilane to the polymethyl methacrylate contained in the polymethyl methacrylate solution is 10:1.5.
[0088] In this embodiment, the mass ratio of PMMA to liquid polycarbosilane is less than 3:10, and the SiC ceramic matrix obtained by cracking cannot form a continuous network structure. The SEM image of the material containing the SiC ceramic matrix obtained in step ③ of this embodiment is as follows: Figure 2 shown.
[0089] Example 5
[0090] Example 5 is substantially the same as Example 1, except that:
[0091] ② A blended precursor is prepared by combining liquid polycarbosilane and polymethyl methacrylate (PMMA) in a mass ratio of 10:20; specifically, the polymethyl methacrylate (PMMA) solid powder is first dissolved in a mixed solvent consisting of acetone and xylene (the volume ratio of acetone to xylene is 10:1.5), and the polymethyl methacrylate solution obtained after the dissolution (the mass fraction of polymethyl methacrylate in the polymethyl methacrylate solution is 60%) is continuously added to the liquid polycarbosilane, and the mixture is stirred evenly at room temperature for 18 hours. The evenly stirred solution is poured into a watch glass, placed in a fume hood, and left at room temperature for 24 hours to obtain a blended precursor, wherein the mass ratio of the liquid polycarbosilane to the polymethyl methacrylate contained in the polymethyl methacrylate solution is 10:20.
[0092] Example 6
[0093] Embodiment 6 is substantially the same as Embodiment 1, except that:
[0094] ③ Using the blended precursor obtained in step ② as the impregnation liquid, the PyC (BN / SiC) obtained in step ① n The reinforcement of the interface layer is impregnated, and a material containing a SiC ceramic matrix is obtained by a PIP process of impregnation / curing / cracking; specifically: (a) using the blended precursor as an impregnation liquid to impregnate the PyC (BN / SiC)n The reinforcement of the interface layer is impregnated, the impregnation is first vacuum impregnation and then high-pressure impregnation, the pressure of the vacuum impregnation is 100Pa, the time is 3h, and the pressure of the high-pressure impregnation is 3MPa, and the time is 3h; (b) after impregnation, curing is performed, the curing is first cured at 110°C for 2h, and then cured at 160°C for 3h, and the curing pressure is 3MPa; (c) after curing, a high-temperature treatment furnace is used to perform atmospheric pressure cracking in an argon inert atmosphere. During the atmospheric pressure cracking process, the temperature is first increased to 350°C at a heating rate of 5°C / min and cracked at 350°C for 6h, and then increased to 1200°C at a heating rate of 5°C / min and cracked at 1200°C for 3h; (d) steps (a) to (c) are repeated twice in sequence, and a total of 3 impregnation / curing / cracking cycles are performed to complete the preparation of the material containing the SiC ceramic matrix; the material containing the SiC ceramic matrix prepared in this way is replaced with the material containing the SiC ceramic matrix having a continuous network structure prepared in Example 1 to carry out subsequent steps.
[0095] Example 7
[0096] Example 7 is substantially the same as Example 1, except that:
[0097] ③ Using the blended precursor obtained in step ② as the impregnation liquid, the PyC (BN / SiC) obtained in step ① n The reinforcement of the interface layer is impregnated, and a material containing a SiC ceramic matrix is obtained by a PIP process of impregnation / curing / cracking; specifically: (a) using the blended precursor as an impregnation liquid to impregnate the PyC (BN / SiC) n The reinforcement of the interface layer is impregnated, and the impregnation is first vacuum impregnation and then high-pressure impregnation. The pressure of the vacuum impregnation is 100Pa and the time is 3h. The pressure of the high-pressure impregnation is 3MPa and the time is 3h; (b) after impregnation, curing is performed, and the curing is first cured at 110°C for 2h and then cured at 160°C for 3h. The curing pressure is 3MPa; (c) after curing, a high-temperature treatment furnace is used to perform atmospheric cracking in an argon inert atmosphere. During the atmospheric cracking process, the temperature is increased to 1200°C at a heating rate of 5°C / min and cracked at 1200°C for 6h; (d) steps (a) to (c) are repeated twice in sequence, and a total of 3 impregnation / curing / cracking cycles are performed to complete the preparation of the material containing the SiC ceramic matrix; the material containing the SiC ceramic matrix prepared in this way is replaced with the material containing the SiC ceramic matrix with a continuous network structure prepared in Example 1 to carry out subsequent steps.
[0098] Comparative Example 1
[0099] ①Same as step ① of Example 1.
[0100] ②Same as step ② of Example 1.
[0101] ③ is the same as step ③ of Example 1.
[0102] ④ Using a polyborosilazane precursor (liquid polyborosilazane) as an impregnation liquid, the material containing the SiC ceramic matrix having a continuous network structure obtained in step ③ is impregnated, and a material containing a SiBCN ceramic matrix having a self-healing function is obtained by an impregnation / curing / cracking PIP process; specifically: (a) using a polyborosilazane precursor as an impregnation liquid, the material containing the SiC ceramic matrix having a continuous network structure obtained in step ③ is impregnated, and the impregnation is first vacuum impregnation and then high-pressure impregnation, the vacuum impregnation pressure is 100 Pa, the time is 3h, and the high-pressure impregnation The impregnation pressure is 3MPa and the time is 3h; (b) after impregnation, curing is performed, the curing temperature is 200℃, the curing time is 3h, and the curing pressure is 4MPa; (c) after curing, a high-pressure cracking furnace is used to crack under an argon inert atmosphere, the cracking temperature is 1200℃, the cracking time is 3h, and the cracking pressure is 5MPa; (d) steps (a) to (c) are repeated three times in sequence, for a total of four impregnation / curing / cracking cycles, to complete the preparation of a material containing a SiBCN ceramic matrix with self-healing function.
[0103] ⑤ Subjecting the material obtained in step ④ comprising the SiBCN ceramic matrix with self-healing function to high-temperature treatment to obtain a ceramic-based composite material; the high-temperature treatment is carried out under an argon inert atmosphere at a temperature of 1450° C. and a time of 3 hours.
[0104] Comparative Example 2
[0105] ①Same as step ① of Example 1.
[0106] ②Same as step ② of Example 1.
[0107] ③ is the same as step ③ of Example 1.
[0108] ④ is the same as step ④ of Example 1.
[0109] ⑤ The material after the first high temperature treatment in step ④ is impregnated with a polyborosilazane precursor as an impregnation liquid, and a material containing a SiBCN ceramic matrix with a self-healing function is obtained by an impregnation / curing / cracking PIP process; specifically: (a) the material after the first high temperature treatment in step ④ is impregnated with a polyborosilazane precursor as an impregnation liquid, and the impregnation is first vacuum impregnation and then high-pressure impregnation, the vacuum impregnation pressure is 100Pa, the time is 3h, and the high-pressure impregnation pressure is 3MPa, and the time is 3h; (b) after impregnation, curing is performed, the curing temperature is 200°C, the curing time is 3h, and the curing pressure is 4MPa; (c) after curing, a high-pressure cracking furnace is used to crack in an argon inert atmosphere, the cracking temperature is 1200°C, the cracking time is 3h, and the cracking pressure is 5MPa; (d) steps (a) to (c) are repeated 3 times in sequence, and a total of 4 impregnation / curing / cracking cycles are performed to obtain a ceramic-based composite material.
[0110] Comparative Example 3
[0111] ①Same as step ① of Example 1.
[0112] ② Using liquid polycarbosilane as the impregnation liquid, the PyC (BN / SiC) obtained in step ① n The reinforcement of the interface layer is impregnated, and a material containing a SiC ceramic matrix is obtained by a PIP process of impregnation / curing / cracking; specifically, (a) liquid polycarbosilane is used as an impregnation liquid to impregnate the PyC (BN / SiC) n The reinforcement of the interface layer is impregnated, and the impregnation is first vacuum impregnation and then high-pressure impregnation. The pressure of the vacuum impregnation is 100Pa and the time is 3h. The pressure of the high-pressure impregnation is 3MPa and the time is 3h; (b) after impregnation, curing is performed, and the curing is first cured at 110°C for 2h and then cured at 160°C for 3h. The curing pressure is 3MPa; (c) after curing, a high-temperature treatment furnace is used to perform atmospheric pressure cracking in an argon inert atmosphere. The atmospheric pressure cracking temperature is 1200°C and the cracking time is 3h; (d) steps (a) to (c) are repeated twice in sequence, and a total of 3 impregnation / curing / cracking cycles are performed to complete the preparation of the material containing the SiC ceramic matrix.
[0113] ③ Subject the material containing the SiC ceramic matrix obtained in step ② to a first high-temperature treatment, wherein the first high-temperature treatment is performed under an argon inert atmosphere, the temperature of the first high-temperature treatment is 1450° C., and the time is 3 hours.
[0114] ④ The material after the first high-temperature treatment in step ③ is impregnated with a polyborosilazane precursor as an impregnation liquid, and a material containing a SiBCN ceramic matrix is obtained by a PIP process of impregnation / curing / cracking; specifically: (a) the material after the first high-temperature treatment in step ③ is impregnated with a polyborosilazane precursor as an impregnation liquid, and the impregnation is first vacuum impregnation and then high-pressure impregnation, the pressure of the vacuum impregnation is 100 Pa, the time is 3h, and the pressure of the high-pressure impregnation is 3MPa, and the time is 3h; (b) after impregnation, curing is performed, the curing temperature is 200°C, the curing time is 3h, and the curing pressure is 4MPa; (c) after curing, a high-pressure cracking furnace is used to crack the material under an argon inert atmosphere, the cracking temperature is 1200°C, the cracking time is 3h, and the cracking pressure is 5MPa; (d) steps (a) to (c) are repeated three times in sequence, and a total of four impregnation / curing / cracking cycles are performed to complete the preparation of the material containing a SiBCN ceramic matrix.
[0115] ⑤ Subject the material containing the SiBCN ceramic matrix obtained in step ④ to a second high-temperature treatment to obtain a ceramic-based composite material; the second high-temperature treatment is carried out under an argon inert atmosphere, the temperature of the second high-temperature treatment is 1450°C, and the time is 3 hours.
[0116] Comparative Example 4
[0117] Comparative Example 4 provides a mullite fiber reinforced ceramic matrix composite material with reference to Example 2 of Chinese Patent CN 113979752 B.
[0118] Comparative Example 5
[0119] Comparative Example 5 provides a mullite fiber reinforced ceramic matrix composite material with reference to Example 2 of Chinese Patent CN 113800934 B.
[0120] Comparative Example 6
[0121] ① Basically the same as Example 1.
[0122] ② Using liquid polycarbosilane as the impregnation liquid, the PyC (BN / SiC) obtained in step ① n The reinforcement of the interface layer is impregnated, and a ceramic matrix composite material is obtained by an impregnation / curing / cracking PIP process; specifically: (a) liquid polycarbosilane is used as an impregnation liquid to impregnate the PyC (BN / SiC) nThe reinforcement of the interface layer is impregnated, and the impregnation is first vacuum impregnation and then high-pressure impregnation. The pressure of the vacuum impregnation is 100Pa and the time is 3h. The pressure of the high-pressure impregnation is 3MPa and the time is 3h; (b) after impregnation, curing is performed, and the curing is first cured at 110°C for 2h and then cured at 160°C for 3h. The curing pressure is 3MPa; (c) after curing, a high-temperature cracking furnace is used to perform normal pressure cracking in an argon inert atmosphere. The normal pressure cracking temperature is 1200°C and the cracking is performed at 1200°C for 3h; (d) steps (a) to (c) are repeated 7 times in sequence, and a total of 8 impregnation / curing / cracking cycles are performed to complete the preparation of the ceramic-based composite material.
[0123] In the preparation of the ceramic matrix composite material in this comparative example, liquid polycarbosilane is used as the impregnation liquid. The structure of the liquid polycarbosilane after cracking is very dense and has no holes. The SEM image of the ceramic matrix composite material prepared in this comparative example is as follows: Figure 3 shown.
[0124] Comparative Example 7
[0125] ① Basically the same as Example 1.
[0126] ② Using polyborosilazane precursor as impregnation liquid to treat the PyC (BN / SiC) obtained in step ① n The reinforcement of the interface layer is impregnated, and a ceramic matrix composite material is obtained by a PIP process of impregnation / curing / cracking; specifically: (a) using a polyborosilazane precursor as an impregnation liquid to impregnate the PyC (BN / SiC) obtained in step ① n The reinforcement of the interface layer is impregnated, and the impregnation is first vacuum impregnation and then high-pressure impregnation, the pressure of the vacuum impregnation is 100Pa, the time is 3h, and the pressure of the high-pressure impregnation is 3MPa, and the time is 3h; (b) after impregnation, curing is performed, the curing temperature is 200℃, the curing time is 3h, and the curing pressure is 4MPa; (c) after curing, a high-pressure cracking furnace is used to crack in an argon inert atmosphere, the cracking temperature is 1200℃, the cracking time is 3h, and the cracking pressure is 5MPa; (d) steps (a) to (c) are repeated 7 times in sequence, and a total of 8 impregnation / curing / cracking cycles are performed to complete the preparation of the ceramic-based composite material.
[0127] In this comparative example, when preparing the ceramic matrix composite material, a polyborosilazane precursor is used as an impregnation liquid. The polyborosilazane precursor is cracked to form a dense block. The SEM image of the ceramic matrix composite material prepared in this comparative example is as follows: Figure 4 shown.
[0128] from Figure 3 and Figure 4It can be seen from the results that if liquid polycarbosilane and polyborosilazane precursors are directly used for impregnation in sequence, the final SiC matrix and SiBCN matrix will be isolated from each other, namely SiC-rich region and SiBCN-rich region, respectively, and the two ceramics cannot be evenly distributed.
[0129] The present invention conducted an oxyacetylene ablation test on the ceramic-based composite materials finally prepared in each embodiment and the ceramic-based composite materials finally prepared in comparative examples 1 to 5, and the linear ablation rate results of the oxyacetylene ablation test at 1400°C / 1000s (the material surface temperature is 1400°C, and the test time is 1000s) are shown in Table 1; the present invention also oxidized the ceramic-based composite materials finally prepared in each embodiment and the ceramic-based composite materials finally prepared in comparative examples 1 to 5 at 1400°C in an air atmosphere for 12 hours, and the weight loss rate results are shown in Table 1.
[0130] Table 1
[0131] Example Linear ablation rate (mm / s) Weight loss rate (%) Example 1 <![CDATA[0.6×10 -4 ]]> 0.13 Example 2 <![CDATA[0.8×10 -4 ]]> 0.16 Example 3 <![CDATA[0.9×10 -4 ]]> 0.18 Example 4 <![CDATA[1.1×10 -4 ]]> 0.24 Example 5 <![CDATA[1.3×10 -4 ]]> 0.28 Example 6 <![CDATA[1.4×10 -4 ]]> 0.31 Example 7 <![CDATA[1.6×10 -4 ]]> 0.35 Comparative Example 1 <![CDATA[5.6×10 -4 ]]> 0.69 Comparative Example 2 <![CDATA[7.8×10 -4 ]]> 0.93 Comparative Example 3 <![CDATA[1.16×10 -3 ]]> 1.06 Comparative Example 4 <![CDATA[3.46×10 -3 ]]> 1.24 Comparative Example 5 <![CDATA[1.05×10 -3 ]]> 0.97
[0132] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0133] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a self-healing ceramic-based composite material having a continuous network structure, characterized in that: The method comprises the following steps: (1) Preparing a pyrolytic carbon (PyC) layer on the surface of the carbon fiber of the carbon fiber preform, and then preparing (BN / SiC) on the basis of the pyrolytic carbon (PyC) layer n Alternating interface layers, resulting in PyC(BN / SiC) n Reinforcement of the interface layer; (2) Liquid polycarbosilane and polymethyl methacrylate are prepared into a blended precursor, and the blended precursor is used as an impregnation liquid for the PyC (BN / SiC) n The reinforcement of the interface layer is impregnated to obtain a material including a SiC ceramic matrix having a continuous network structure through a PIP process of impregnation / solidification / cracking; (3) subjecting the material including the SiC ceramic matrix having a continuous network structure to a first high temperature treatment; (4) impregnating the material after the first high-temperature treatment with a polyborosilazane precursor as an impregnation liquid, and obtaining a material including a SiBCN ceramic matrix with a self-healing function through an impregnation / curing / cracking PIP process; (5) Subjecting the material including the SiBCN ceramic matrix having a self-healing function to a second high-temperature treatment to obtain a self-healing ceramic-based composite material having a continuous network structure.
2. The preparation method according to claim 1, characterized in that: The carbon fiber preform is a needle-punched structure, a stitched structure, a 2.5D structure or a puncture structure; and / or The volume fraction of the carbon fiber in the carbon fiber preform is 25-50%.
3. The preparation method according to claim 1, characterized in that: n represents the number of BN / SiC layers, n≥1 and is a natural number; The thickness of the pyrolytic carbon PyC layer is 30 to 80 nm; The thickness of the single BN layer is 50 to 250 nm; and / or The thickness of the single SiC layer is 50 to 200 nm.
4. The preparation method according to claim 1, characterized in that: Step (1) includes the following sub-steps: (a) placing a carbon fiber preform in a first atmosphere including propane and argon for deposition to obtain a first sample with a pyrolytic carbon (PyC) layer deposited on the surface; (b) placing the first sample in a second atmosphere including boron trichloride, ammonia, hydrogen and nitrogen for deposition to obtain a second sample with a BN layer deposited on the surface; (c) placing the second sample in a third atmosphere including trichloromethylsilane, argon and hydrogen for deposition to obtain a third sample with a SiC layer deposited on the surface; (d) repeating step (b) and step (c) n-1 times, then heating to 1200-1400° C. and keeping the temperature for 1-4 hours to obtain the PyC (BN / SiC) n The reinforcement of the interface layer.
5. The preparation method according to claim 4, characterized in that: In step (a), the molar ratio of the propane to the argon is 1:(1-2), the deposition temperature is 900-1100° C., and the deposition pressure is 5-10 kPa; In step (b), the molar ratio of the boron trichloride to the ammonia is 1:(2-3), the deposition temperature is 750-900° C., and the deposition pressure is 5-10 kPa; and / or In step (c), the molar ratio of the trichloromethylsilane to the hydrogen is 1:(2-3); the deposition temperature is 1000-1200° C., and the deposition pressure is 5-10 kPa.
6. The preparation method according to claim 1, characterized in that: The blended precursor is prepared by first dissolving polymethyl methacrylate in a mixed solvent consisting of acetone and xylene to obtain a polymethyl methacrylate solution, then adding the polymethyl methacrylate solution into liquid polycarbosilane and stirring for 10 to 20 hours, and then leaving it for 12 to 24 hours to obtain a blended precursor; and / or The mass ratio of the liquid polycarbosilane to polymethyl methacrylate is 10:(3-15).
7. The preparation method according to claim 1, characterized in that: In step (2): The impregnation is first vacuum impregnation and then high-pressure impregnation, the pressure of the vacuum impregnation is 10-200 Pa, the time is 2-4 hours, and the pressure of the high-pressure impregnation is 2-5 MPa, the time is 2-4 hours; The curing is firstly curing at 100-120° C. for 1-4 hours, and then curing at 150-180° C. for 1-4 hours, and the curing pressure is 2-5 MPa; The pyrolysis is carried out at 300-320°C for 1-3h, 340-360°C for 1-3h, 380-400°C for 1-3h and 1000-1500°C for 2-6h, and the heating rate in the pyrolysis temperature range of 300-400°C is 0.2-0.4°C / min; and / or The PIP process is repeated 2 to 4 times.
8. The preparation method according to claim 1, characterized in that: In step (4): The impregnation is first vacuum impregnation and then high-pressure impregnation, the pressure of the vacuum impregnation is 10-200 Pa, the time is 2-4 hours, and the pressure of the high-pressure impregnation is 2-5 MPa, the time is 2-4 hours; The curing temperature is 180-220°C, the curing time is 1-4 hours, and the curing pressure is 3-6 MPa; the cracking temperature is 1000-1300°C, the cracking time is 2-6 hours, and the cracking pressure is 3-6 MPa; and / or The PIP process is repeated 3 to 5 times.
9. The preparation method according to claim 1, characterized in that: The temperature of the first high temperature treatment and / or the second high temperature treatment is 1400-1500° C., and the time is 2-4 hours.
10. A self-healing ceramic-based composite material having a continuous network structure obtained by the preparation method according to any one of claims 1 to 9; preferably, the self-healing ceramic-based composite material having a continuous network structure has a linear ablation rate of less than 1×10 -4 mm / s.
Citation Information
Patent Citations
A mullite fiber reinforced ceramic matrix composite material and its preparation method
CN113800934B
A mullite fiber reinforced ceramic matrix composite material and its preparation method
CN113979752B